Hubungan antara Kepercayaan Diri dan Kemampuan Berpikir Kritis dalam Pembelajaran: Studi di SMA Negeri 1 Sumberejo - Safitri, Rizki Mei; Sutiarso, Sugeng (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2023)
This study aimed to determine the relationship between students' self-confidence and critical thinking skills in the learning process in SMA Negeri 1 Sumberejo. The research participants consisted of 108 students in class XI MIPA SMA Negeri 1 Sumberejo, Tanggamus Regency in the 2021/2022 academic year, which was divided into three classes. Purposive sampling was used to select the research sample. This study used a descriptive correlational design with a correlational study method. The instruments used consisted of a descriptive test to measure critical thinking skills and a self-confidence questionnaire. The data for this study consisted of quantitative data collected by filling out student self-confidence questionnaires and descriptive tests on critical thinking skills on the topic of linear programs as primary data. Data analysis was conducted using the Pearson product-moment correlation test, with a significance level of Î± = 0.05. The results showed a significant relationship between self-confidence and students' critical thinking skills in learning, with a correlation coefficient of 0.932 and a Sig. (2-tailed) value of 0.000, respectively. This indicates that the higher the students' self-confidence level, the higher their critical thinking skills.